Beothuk-European Contact in the 16th Century:: A Re-evaluation of the Documentary Evidence - Gilbert, William (Acadiensis, 2011)
Abstract It is generally believed that hostility between Newfoundland’s Beothuk people and Europeans had its origin in the protohistoric period. This article re-evaluates the documentary evidence from the 16th century in order to assess this notion. Although the sources are fragmentary and often difficult to interpret, the evidence indicates that early Beothuk-European relations were not characterized by hostility and that the well-documented instances of hostility between the Beothuk and Newfoundland settlers during the late 18th and early 19th centuries have been wrongly assumed to indicate a state of perpetual conflict that extended back to the contact period.